PMD tolerance of polarization division multiplex transmission using return-to-zero coding - Hinz, S; Sandel, D; Wust, F; Noé, Reinhold (OPTICS EXPRESS)

A low-voltage torsional actuator for application in RF-microswitches - Plotz, R; Michaelis, S; Aigner, R; Timme, HJ; Binder, J; Noé, Reinhold (SENSORS AND ACTUATORS A-PHYSICAL)

84fs PMD detection sensitivity in 2 x 40 Gbit/s RZ polarisation multiplex transmission experiment - Sandel, D; Noé, Reinhold; Mirvoda, V; Hinz, S; Wust, F (ELECTRONICS LETTERS)

Kunst-Macht-Gewalt. Der ästhetische Ort der Aggressivität - Öhlschläger, Claudia (Arbitrium)

Spezifikation von Echtzeiteigenschaften mit OCL für eine MFERT-basierte Fallstudie - Flake, Stephan; Müller, Wolfgang
Die Object Constraint Language (OCL) wurde entwickelt, um Modellierer bei der Spe- zifikation von Modelleigenschaften im Kontext gegebener UML Diagramme zu un- terst ̈utzen [3]. Jedoch ist es leider nicht m ̈oglich, Eigenschaften, die das dynamische Verhalten betreffen, mit der derzeitigen Version von OCL auszudr ̈ucken. Wir pr ̈asentieren eine Erweiterung von OCL Version 1.4 zur Spezifikation von zu- standsbasierten, zeitbehafteten Eigenschaften. Obwohl OCL und unsere Erweiterung in erster Linie im Rahmen der UML entwickelt worden sind, ist es auch m ̈oglich, mit dieser Sprache Eigenschaften f ̈ur andere objektbasierte Formalismen zu beschrei- ben. Wir veranschaulichen dies anhand einer Anwendung bei der Modellpr ̈ufungsspe- zifikation in Verbindung mit MFERT, einer praxisrelevanten Notation, die im Projekt GRASP zur Modellierung von Produktionsabl ̈aufen eingesetzt wird.

Generation of Interactive Visual Interfaces for Resource Management - Dangberg, Andreas; Müller, Wolfgang (Proceedings of ISI 2001)
This paper introduces the VIVID (Visual Interactive VIew Development) framework for generation and customization of advanced visual interactive environments for resource manipulation in databases. The framework covers the definition of symbols, their mapping to database objects, specification of spatial relationships among them, layout assignment as well as the definition of drag&drop-based user interactions.

Sinn und Sinnlichkeit. Der weibliche Körper in der deutschen Literatur der Bürgerzeit - Morrien, Rita

Chirality in Liquid Crystals: Introduction - Bahr, C.; Kitzerow, Heinz-Siegfried (Chirality in Liquid Crystals)

Twist Grain Boundary Phases - Kitzerow, Heinz-Siegfried (Chirality in Liquid Crystals)

Theologische Musik? Neue Musik? Messiaen, die evangelische Kirchenmusik und die Moderne - Grotjahn, Rebecca (Le Sacre. Musik – Ritus – Religiosität; Biennale Neue Musik Hannover 2001)

Die Soubrette Antonie Held und ihr Kontrakt mit dem Hoftheater zu Hannover - Grotjahn, Rebecca (Viva voce)

Angelica Catalani – Das Bild der Diva - Grotjahn, Rebecca (Viva voce)

Low-rank approximation of improper complex random vectors - Schreier, Peter J.; Scharf, Louis L. (Proc. 35th\ Asilomar Conf.\ Signals Syst.\ Computers)
In reduced-rank signal processing for radar, sonar, and digital communications, we seek the right tradeoff between model bias and model variance for reconstructing signals from noisy data. Here, we extend the classical theory by considering the low-rank approximation of complex random vectors, which may or may not be proper. We show that, in general, widely linear approximation is superior to strictly linear approximation, unless the vector to be approximated is proper, in which case the optimum procedure is strictly linear. We analyze the case where the approximated random vector becomes proper in its internal coordinate system. This class of random vector, which we call generalized proper, possesses qualities similar to proper random vectors.

A Database for Field Extensions of the Rationals - Klüners, Jürgen; Malle, Gunter (LMS Journal of Computation and Mathematics)
This paper announces the creation of a database for number fields. It describes the contents and the methods of access, indicates the origin of the polynomials, and formulates the aims of this collection of fields.
Keywords: Computational Theory and Mathematics; General Mathematics

Soziale Selbstorganisation im informationsgesellschaftlichen Kapitalismus (Social Self-Organization and Informational Capitalism) - Fuchs, Christian

Mesoporous Aluminophosphate Molecular Sieves Synthesized under Nonaqueous Conditions - Tiemann, Michael; Schulz, Marcus; Jäger, Christian; Fröba, Michael (Chemistry of Materials)
Long-chain n-alkylamine surfactants have been used as structure-directing agents in the synthesis of mesoporous aluminophosphates by a highly cooperative formation mechanism in an alcoholic system. Small amounts of water in the synthesis mixture play a significant role in the hydrolysis of the aluminum precursor (Al[OiPr]3) and are important for the quality of the mesostructured products. The materials exhibit disordered mesostructures, the stability and structural order of which can be improved by a postsynthetic thermal treatment. The products are then stable enough for the removal of the surfactant molecules by acidic solvent extraction, yielding surface areas up to 690 m2/g.

Mesostructured Aluminophosphates Synthesized with Supramolecular Structure Directors - Tiemann, Michael; Fröba, Michael (Chemistry of Materials)
Over the past few years a growing number of scientists have dedicated their attention to the synthesis of mesostructured aluminophosphates following the concept of supramolecular structure direction. Their research has produced a large variety of synthetic approaches and yielded materials with various structural properties. Today a substantial number of publications have accumulated; this short review provides a general summary of the literature with the aim to display the opportunities for future work.

Coulomb correlation signatures in the excitonic optical nonlinearities of semiconductors - Meier, Torsten; Koch, S.W. (Ultrafast Physical Processes in Semiconductors)
This chapter focuses on the carrier interaction effects—that is, the many-body Coulomb correlations and their influence on band-gap semiconductor optical nonlinearities. The near band-gap semiconductor response is determined by the optical interaction with the resonant or near resonant material polarization that may result in the excitation of carriers (electron–hole pairs) and/or transient coherent nonlinearities. The microscopic analysis of these effects requires the investigation of the relevant quasi-particles and their interactions. Whereas the basic occurrence of a blue shift can be motivated already based on a simple two-level model, a more detailed understanding of the optical Stark effect in semiconductors requires a microscopic modeling of the relevant bands as well as the inclusion of the many-body Coulomb interaction. Compensations among the first- and higher-order Coulomb terms at the spectral positions of the exciton are obtained in the differential absorption induced by incoherent occupations.

Spectral signatures of χ(5) processes in four-wave mixing of homogeneously broadened excitons - Meier, Torsten; Langbein, W.; Koch, S.W.; Hvam, J.M. (Journal of the Optical Society of America B)
The influence of fifth-order coherences on the spectrally resolved four-wave mixing response of predominantly homogeneously broadened quasi-two-dimensional excitons is studied. Fifth-order signatures are discussed as a function of spectral position and excitation polarization. An exciton–biexciton beating for positive delay times is the dominant effect, which is pronounced at the exciton–biexciton transition for collinearly polarized excitation and at the exciton transition for cross-linearly polarized excitation. For negative delay times and collinearly polarized excitation a pronounced exciton–biexciton beating at the exciton resonance is observed that is vanishing for long negative delays owing to the faster dephasing in the two-exciton continuum compared with the bound biexciton state. These results are in qualitative agreement with microscopic model calculations that include the coherent dynamics of one- and two-exciton resonances up to the fifth order in the optical field.

Linear and nonlinear optical properties of semiconductor nanorings with magnetic field and disorder-Influence on excitons and biexcitons - Meier, Torsten; Thomas, P.; Koch, S.W. (The European Physical Journal B - Condensed Matter and Complex Systems)
Linear and nonlinear optical absorption spectra are studied theoretically for semiconductor nanorings penetrated by a magnetic field. Due to the Aharanov-Bohm effect the spectral position as well as the oscillator strength of the exciton change periodically as function of the magnetic flux enclosed by the ring. In the nonlinear differential absorption spectra it is found that the magnetic field strongly modifies Coulomb many-body correlations. In particular, the magnetic-field-induced increase of the exciton binding energy is accompanied by a decrease of the biexciton binding energy. The persistence of these effects in the presence of energetic disorder is analyzed.

Coherent Dynamics of Photoexcited Semiconductor Superlattices with Applied Homogeneous Electric Fields - Meier, Torsten; Thomas, P.; Koch, S.W. (Ultrafast Phenomena in Semiconductors)
In this chapter a microscopic many-body theory is reviewed that allows one to compute the linear and nonlinear optical properties of semiconductor superlattices in the presence of homogeneous electric fields applied in the growth direction. The theory includes the process of optical excitation, the Coulomb interaction among the carriers, carrier-phonon coupling, and the acceleration induced by the electric field. Coherent phenomena induced by dc and ac fields, like Bloch oscillations and dynamical localization, are introduced and discussed. The theoretical analysis concentrates on the signatures and observability of such phenomena in linear and nonlinear optical experiments.

Influence of Light Holes on the Heavy-Hole Excitonic Optical Stark Effect - Meier, Torsten; Brick, P.; Ell, C.; Khitrova, G.; Gibbs, H.M.; Sieh, C.; Koch, S.W. (Physical Review B)
Pump-probe experiments on high-quality InxGa1−x As quantum wells are used to investigate the influence of light-hole excitons on the optical Stark effect. For anticircular polarization of pump and probe pulses and a moderate negative detuning of the pump energy, a redshift of the heavy-hole resonance is observed. However, with increasingly negative detuning a transition from this redshift to a blueshift is found. Microscopic calculations that include both heavy holes and light holes reproduce the experimental results. The theoretical analysis shows that the observation of the redshift depends very sensitively on the detuning of the pump pulses and the heavy-hole to light-hole splitting.

Coherent Dynamics of Magnetoexcitons in Semiconductor Nanorings - Meier, Torsten; Maschke, K.; Thomas, P.; Koch, S.W. (The European Physical Journal B - Condensed Matter and Complex Systems)
The coherent dynamics of magnetoexcitons in semiconductor nanorings following pulsed optical excitation is studied. The calculated temporal evolution of the excitonic dipole moment may be understood as a superposition of the relative motion of electrons and holes and a global circular motion associated with the magnetic-field splitting of these states. This dynamics of the electron-hole pairs can be generated either by local optical excitation of an ordered ring or, alternatively, by homogeneous excitation of rings with broken rotational symmetry due to disorder or band tilting.

Gemeindekulturpädagogik. Henning Schröer zum 70. Geburtstag

Kirchentag - Schroeter-Wittke, Harald (Evangelischer Taschenkatechismus)

Thadden-Trieglaff, Reinold von (1891-1976) - Schroeter-Wittke, Harald (Theologische Realenzyklopädie)

Die Orgel und die Kasualien - Schroeter-Wittke, Harald (Forum Kirchenmusik)

Kirchentag - Schroeter-Wittke, Harald (Religion in Geschichte und Gegenwart)

Liturgisches Konzert. Vierhändige Klaviermusik zwischen öffentlicher Religion und privater Andacht (CD mit Werken von Johannes Brahms: Variationen über ein Thema von Schumann op. 23 (1861); Claude Debussy: Six épigraphes antiques (1914) und Paul Hindemith: Symphonie "Mathis der Maler" (1934) - Schroeter-Wittke, Harald; Wicke, Berthold

PaxAN! Das "andere" Börsenspiel zum Kirchentag 2001 - Schroeter-Wittke, Harald (Kirchentags-Programmheft Frankfurt 2001)

Dynamics of Coulomb-correlated electron-hole pairs in disordered semiconductor nanowires - Meier, Torsten; Varga, I.; Schlichenmaier, C.; Maschke, K.; Thomas, P.; Koch, S.W. (Proceedings of the XXXVIth Rencontres de Moriond on Electronic Correlations: From Meso-Physics to Nano-Physics)
The dynamics of optically generated electron-hole pairs is investigated in a disordered semiconductor nanowire. The particle pairs are generated by short laser pulses and their dynamics is followed using the Heisenberg equation of motion. Is is shown that Coulomb-correlation acts against localization in the case of the two-interacting particles (TIP) problem. Furthermore, currents are generated using a coherent combination of full-gap and half-gap pulses. The subsequent application of a full-gap pulse after time τ produces an intraband echo phenomenon 2τ time later. The echo current is shown to depend on the mass ratio between the electrons and the holes.

Identitätskonstruktion und Prophetie - Die Elias-Homilien von Gottfried Menken, Friedrich Wilhelm Krummacher und Johannes F.A. de le Roi - Schroeter-Wittke, Harald (Monatshefte für Evangelische Kirchengeschichte des Rheinlandes)

Correlation effects in the excitonic optical properties of semiconductors - Meier, Torsten; Kira, M.; Koch, S.W. (Journal of Optics B: Quantum and Semiclassical Optics)
A microscopic many-body theory for the optical and electronic properties of semiconductors is reviewed with an emphasis on the role of correlation effects. At the semiclassical level, the semiconductor Bloch equations include many-body effects via bandgap and field renormalization as well as correlation contributions representing two electron-hole pair amplitudes, excitonic populations, and coupled interband and intraband coherences. These Coulomb interaction induced carrier correlations lead to characteristic signatures in nonlinear semiconductor spectroscopy. At the fully quantum mechanical level the dominant light-matter correlations are described by coupled semiconductor Bloch and luminescence equations. Excitonic emission properties of quantum well and microcavity systems are discussed, including effects such as coherent signatures in the secondary emission and coherent control of the emitted light.

Coherent spectral oscillations in multiwave mixing - Meier, Torsten; Wagner, H.P.; Tranitz, H.-P.; Reichelt, Matthias; Koch, S.W. (Physical Review B)
The nonlinear optical response of a ZnSe single quantum well is investigated by spectrally resolving a wave-mixing signal using a three-beam configuration. A delayed third pulse with direction k3 leads to coherent oscillations in the spectrum emitted in 2k2–k1. Polarization-dependent measurements highlight the importance of higher-order Coulomb correlations as the dominant coupling mechanism between the three pulses. The experimental results are well explained by microscopic calculations including four-particle correlations up to fifth order in the fields.

The excitonic Stark effect: Absorption splitting and the influence of the light-hole exciton - Meier, Torsten; Chatterjee, S.; Brick, P.; Ell, C.; Gibbs, H.M.; Khitrova, G.; Sieh, C.; Koch, S.W. (Coherent optical nonlinearities in normal mode microcavities)
Summary form only given. Since the original discovery of the excitonic optical Stark effect, substantial progress has been made in the understanding of this ultrafast nonlinear optical effect. Recently, a red shift of the excitonic absorption line has been reported using low intensity excitation detuned 4.5 meV below the 1s-heavy-hole (hh) resonance and cross-circularly-polarized pulses. This was attributed to higher-order Coulomb correlations, interpretable as bound and unbound two-exciton states and memory effects. For co-circularly polarized pulses the well-known blue shift was found. Here we present a related effect occurring in the higher-intensity regime. Standard pump-probe experiments were performed on high-quality 8.5 nm-thick In/sub 0.04/Ga/sub 0.96/As multiple quantum well (MQW) samples.

Coherent optical nonlinearities in normal mode microcavities - Meier, Torsten; Lee, Y-.S; Norris, T.B.; Khitrova, G.; Gibbs, H.M.; Sieh, C.; Koch, S.W.; Jahnke, F. (Quantum Electronics and Laser Science Conference)
Summary form only given. When a quantum-well exciton transition is resonant with a single mode of a high-Q microcavity the linear reponse of the coupled system may be described in terms of normal modes ("cavity polaritons"), which arise as a result of the interplay of absorption and dispersion of the exciton transition within the cavity. The nonlinear response of these systems has often been discussed in terms of "polaritonic nonlinearities". It is desirable to investigate the nonlinearities of normal-mode microcavities (NMC's) at the same level and to determine if the microscopic theory accounting for the bare-QW response also quantitatively accounts for the normal-mode nonlinear response. We report here an extensive series of pump-probe experiments, investigating the time-resolved reflectivity of an NMC as a function of pump and probe polarization and pump fluence.

Excitons and biexcitons as mesoscopic probes of disorder in semiconductor heterostructures - Meier, Torsten; Finger, E.; Kraft, S.; Hofmann, M.; Nau, S.; Bernatz, G.; Stolz, W.; Thomas, P.; Koch, S.W.; Rühle, W.W. (Quantum Electronics and Laser Science Conference)
Summary form only given. Optical and electronic properties of semiconductor heterostructures are strongly influenced by inherent disorder effects. The disorder consists of alloy disorder in ternary or quaternary compound semiconductors and interface roughness in semiconductor quantum wells. The spatial scales of disorder depend on the growth process. The disorder scale has up to now been extremely difficult to determine by macroscopic optical experiments. Here, we use excitons and biexcitons as mesoscopic probes in coherent excitation spectroscopy (CES) to reveal the spatial scale of disorder.

Technisch vermittelte Entkörperlichung – Emanzipation oder Risiko? (Technologically mediated disembodiment – emancipation or risk?) - Fuchs, Christian (Utopie Kreativ 129/130)

Theorien der Globalisierung (Theories of globalization) - Fuchs, Christian; Hofkirchner, Wolfgang (Z 48)

Review of “Mythen der New Economy“ (Myths of the new economy, by Joachim Bischoff) - Fuchs, Christian (Das Argument 242)

‘Die Nacht. Die Kunst des sich Zurechtmachens’ - Kraft, Kerstin

‘zeit.schnitte’ - Kraft, Kerstin

Was ist Geld? Vortrag und Spiel im Forum Geld am 15. juni in der Festhalle - Schroeter-Wittke, Harald; Hörisch, Jochen (Deutscher Evangelischer Kirchentag Frankfurt am Main 2001. Dokumente)

"Boh glaub'se": Vielfalt in Sachen des Unbedingten und Letzten - Schroeter-Wittke, Harald (Kultur in Nordrhein-Westfalen. Zwischen Kirchturm, Förderturm und Fernsehturm)

Kasualgottesdienst und Kausalmusik. Gemeindekulturpädagogisches Thema mit 6 Variationen - Schroeter-Wittke, Harald (Gemeindekulturpädagogik)

Über theologische Weltmeisterschaft und andere interessante Theologenbräuche - Schroeter-Wittke, Harald (Balancé. Gespräche über Theologie, die die Welt braucht)

Predigt als Unterhaltung. Ein Plädoyer für homiletisches Entertainment - Schroeter-Wittke, Harald (Predigen im Plural. Homiletische Aspekte)

Frank Thomas Brinkmann: Praktische Homiletik. Ein Leitfaden zur Predigtvorbereitung, Stuttgart u.a 2000 - Schroeter-Wittke, Harald (Pastoraltheologie)

Ko-Ordinationspredigt III (Mt 9,13) - Schroeter-Wittke, Harald (Festschrift für Superintendent Dr. Stephan Bitter)

Ingo Reuter: Predigt verstehen. Grundlagen einer homiletischen Hermeneutik, Leipzig 2000. - Schroeter-Wittke, Harald (Pastoraltheologie)

Thomas Klie (Hg.): Darstellung und Wahrnehmung. Religion im medialen Crossover, Münster u.a. 2000 - Schroeter-Wittke, Harald (Loccumer Pelikan)

Konversi - Schroeter-Wittke, Harald; Hörisch, Jochen (epd-Dokumentation)

Hans-Günter Heimbrock / Matthias von Kriegstein (Hg.): Predigen lernen, Gottesdienst feiern lernen. Neue Wege in der theologischen Ausbildung - Schroeter-Wittke, Harald (Pastoraltheologie)

Vector bundles on singular projective curves - Burban, Igor; Drozd, Yu.; Greuel, G.-M. (Applications of algebraic geometry to coding theory, physics and computation)

»Soviel Gefühle kann's nicht geben!« Typisierung des Feierns und Jubelns im Fernsehsport - Adelmann, Ralf; Keilbach, Judith; Stauff, Markus (montage/av. Zeitschrift für Theorie und Geschichte audiovisueller Kommunikation)

Spielleiter im Fernsehsport - Adelmann, Ralf; Stauff, Markus (Gottschalk, Kerner & Co)

body natural / body video / body politic - Adelmann, Ralf (https://nachdemfilm.de/issues/no-3-video-und-ueberwachung)

»scapes« – Landschaften unter medialen Bedingungen - Adelmann, Ralf (Kulturrevolution)

Die Schulreform in England und ihre Auswirkungen auf die Leistungsbewertung - Freitag, Christine (Anpassen, verändern, abschaffen? Schulische Leistungsbewertung in der Diskussion)

Kindheit und Jugend im Wandel politischer Konzeptionen: Erziehungswissenschaftliche Deutungen - Freitag, Christine (Kindheit zwischen Mythos und Realität)

Erziehen und Unterrichten: Überlegungen zu den zentralen Aufgaben des Lehrers - Freitag, Christine (Seminar – Lehrerbildung und Schule, 1/2001)

„Die mit den Zeichen tanzen“. Ein Beitrag zum Verhältnis von informationstechnischer Bildung und Medienerziehung - Herzig, Bardo (Medienpädagogik – Online-Zeitschrift für Theorie und Praxis der Medienbildung, Ausgabe 2/2001)

Medien machen Schule. Grundlagen, Konzepte und Erfahrungen zur Medienbildung

Lernförderliche Potentiale von Multimedia. Medienbezogene, lerntheoretische und didaktische Aspekte - Herzig, Bardo (Aktuelle Aspekte medienpädagogischer Forschung. Interdisziplinäre Beiträge aus Forschung und Praxis)

Medienbildung und Informatik. Zur Fundierung einer integrativen Medienbildungstheorie - Herzig, Bardo (Informatikunterricht und Medienbildung. GI-Edition Lecture Notes in Informatics)

Medienerziehung und informatische Bildung – ein semiotischer Beitrag zu einer integrierten Medienbildungstheorie - Herzig, Bardo (Medien machen Schule. Grundlagen, Konzepte und Erfahrungen zur Medienbildung)

Medien in Kinderwelten. Über einen verantwortungsbewussten und reflektierten Umgang mit Medienangeboten - Herzig, Bardo (Grundschule zwischen Bilderbuch und Internet)

Medienhandeln und Verantwortung. Zur Förderung eines verantwortungsbewussten Umgangs mit (neuen) Medien - Herzig, Bardo (Der Einfluss der Medien. Vertrauen und soziale Verantwortung)

Lesarten schulischer Medienbildung - Herzig, Bardo (Medien machen Schule. Grundlagen, Konzepte und Erfahrungen zur Medienbildung)

Beurteilung von Medienkompetenz - Herzig, Bardo (Anpassen, verändern, abschaffen? Schulische Leistungsbewertung in der Diskussion)

Selbst gesteuertes Lernen mit Multimedia. Lerntheoretisch und didaktisch begründete Anforderungen an Lernumgebungen zum selbst gesteuerten Lernen - Herzig, Bardo (Neue Medien – Perspektiven für das Lernen und Lehren in der beruflichen Bildung)

Werterziehung in der Schule. Eine erwägungsorientierte Auseinandersetzung mit Lawrence Kohlberg - Herzig, Bardo (Erwägungsorientierung in Philosophie und Sozialwissenschaften)

Medienerziehung im Jahrhundert des Kindes – eine systematische und historische Analyse - Herzig, Bardo; Tulodziecki, G. (Kindheit zwischen Mythos und Realität)

Medienerziehung im Jahrhundert des Kindes – eine systematische und historische Analyse - Herzig, Bardo; Tulodziecki, G. (1900-2000. „Das Jahrhundert des Kindes“. Verheißungen, Realität, Herausforderungen. Zukunftsforum Politik Nr. 28 (2001))

Sicherheit und Anwendungen des Advanced Encryption Standard (AES) Rijndael - Krummel, Volker
Keywords: Diplomarbeit

Brauer Addition-Subtraction Chains - Otto, Martin
Keywords: Diplomarbeit

Flashback - Bartz, Christina (Gedächtnis und Erinnerung. Ein interdisziplinäres Lexikon)

Imageaufbau – eine Aufgabe für die angewandte Sprachwissenschaft? - Schuster, Britt-Marie (Raum, Zeit, Medium – Sprache und ihre Determinanten. Festschrift für Hans Ramge zum 60. Geburtstag)
Keywords: Kommunikationsgeschichte

Die Entstehung und Entwicklung der psychiatrischen Fachsprache im 19. Jh.: Von der präskriptiven Anthropologie zur ärztlichen Beschreibung - Schuster, Britt-Marie (Historische Soziolinguistik des Deutschen V)
Keywords: Fachkommunikation

Top of The Pops - Top of The Spots - Top of The Stocks: Zur Popularität von Subkulturen für das Werbesystem - Jacke, Christoph (Werbung, Mode und Design)

White Trash und Old School: Prominente und Stars als Aufmerksamkeitsattraktoren in der Werbung - Jacke, Christoph (a/effektive Kommunikation: Unterhaltung und Werbung)

Zwischen Kaugummi und Club: der Fotograf als Beobachter von Alltäglichem und Besonderem - Jacke, Christoph (Telepolis)

Open Your Eyes! Medienkulturen als Lebensfolien - Jacke, Christoph (Telepolis)

Prominente und Stars. Aufmerksamkeitskonglomerate und Werbeknotenpunkte - Jacke, Christoph (Telepolis)

Neu! - ein Mythos kehrt zurück - Jacke, Christoph (Telepolis)

Industriegeschichte erleben. Das Rheinische Industriemuseum als außerschulischer Lernort - Hartung, Olaf; Krause, Markus (Geschichte, Politik und ihre Didaktik)

Didaktik und Museum: ein „absurdes“ Verhältnis? Zum Verfall des Didaktik-Begriffs im Museum - Hartung, Olaf (Geschichte, Politik und ihre Didaktik)

„In Hülle und Fülle“. Lebensmittelindustrie und Einzelverpackung - Hartung, Olaf (industrie-kultur)

Homo conspirans. Zur Evolution 'der Paranoia' und 'des Menschen' in Zeiten seiner Exkommunikation - Bartz, Christina; Hahn, Torsten (Mediale Anatomien. Menschenbilder als Medienprojektionen)

Kommunikative Funktionen des Zeitungskommentars - Schuster, Britt-Marie; Ramge, Hans (Medienwissenschaft. Ein Handbuch zur Entwicklung der Medien und Kommunikationsformen)
Keywords: Historische Medienlinguistik

Raum, Zeit, Medium – Sprache und ihre Determinanten. Festschrift für Hans Ramge zum 60. Geburtstag - Schuster, Britt-Marie; Richter , Gerd; Riecke, Jörg
Keywords: Kommunikationsgeschichte

Das Bosman-Urteil und die Folgen für die Nachwuchsförderung im Spitzensport. Bericht aus dem laufenden Forschungsprojekt. - Cachay, Klaus; Riedl, Lars (Spitzensport. Chancen und Probleme)

Das Flaschenhalssyndrom. Zur Problematik globalisierter Spielermärkte und nationaler Auswahlmannschaften - Cachay, Klaus; Riedl, Lars (Verschwinden nationale Auswahlmannschaften in einer ‚offenen’ Gesellschaft?)

Das Flaschenhalssyndrom. Zur Problematik globalisierter Spielermärkte und nationaler Auswahlmannschaften - Cachay, Klaus; Riedl, Lars (Jahrbuch 2001)

Globale Spielermärkte und nationale Nachwuchsförderung. Das Bosman-Urteil und die Folgen - Cachay, Klaus; Riedl, Lars (Leistungssport)

Cachay, K. & Riedl, L. (2001). Bosman-Urteil und Nachwuchsförderung. Folgen der Abschaffung von Ausländerklauseln für die Nachwuchsrekrutierung in den Sportspielen. In: Bundesinstitut für Sportwissenschaft (Hrsg.): BISp Jahrbuch 2000 (S. 239-242). Köln: - Cachay, Klaus; Riedl, Lars (BISp Jahrbuch 2000)

Weltbild und Metapher. Untersuchungen zur Philosophie im 18. Jahrhundert. (Rezensionen: Ralf Konersmann: „Aushilfe für die Rede gesucht. Vanessa Albus liest die Metaphern der Philosophen als Weltbilder“, in: FAZ, 02.09.2002, Nr. 203, S. 36. Felix Heidenreich: „Der Schatten der Philosophie. Neuere Literatur zum Phänomen der Metapher“, in: Philosophische Rundschau, Eine Zeitschrift für philosophische Kritik, 51/3, 2004, S. 212-233. Martin Konitzer: „Review article: Giambattista Vico’s open agenda of modernity“, in: Semiotica, 157, 1/4, 2005, S. 571-575.) - Albus, Vanessa

Der logische Aufbau von Leibniz’ Metaphysik. - Blank, Andreas

“Substance Monism and Substance Pluralism in Leibniz’s Metaphysical Papers 1675–1676.” - Blank, Andreas (Studia Leibnitiana)

Global Player - Local Hero. Der Sportverein zwischen Spitzensport, Publikum und Vemarktung - Cachay, Klaus; Riedl, Lars; Thiel, Ansgar; Wagner, Christian (Forschung an der Universität Bielefeld)